Lung volume reduction and infection localization revealed in Big data CT imaging of COVID-19 - Shi, Feng; Wei, Ying; Xia, Liming; Shan, Fei; Mo, Zhanhao; Yan, Fuhua; Shen, Dinggang (International journal of infectious diseases, 2021)
•Analysis of massive CT lung image among COVID-19, CAP, and nonpneumonia subjects.•Significantly reduced lung volume was found in COVID-19 patients.•Significantly increased lung mass and density were found in COVID-19 patients.•The infections of COVID-19 patients tend to present as bilateral lower lobes. The ongoing worldwide COVID-19 pandemic has become a huge threat to global public health. Using CT image, 3389 COVID-19 patients, 1593 community-acquired pneumonia (CAP) patients, and 1707 nonpneumonia subjects were included to explore the different patterns of lung and lung infection. We found that COVID-19 patients have a significant reduced lung volume with increased density and mass, and the infections tend to present as bilateral lower lobes. The findings provide imaging evidence to improve our understanding of COVID-19.